Peran Mikroorganisme dalam Meningkatkan Produktivitas Tanaman : Pendekatan Bioteknologi Berbasis Mikrobiologi Pertanian - Ester Twenty Aprilian Zendrato; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Crop productivity is one of the key components in supporting the sustainability of the agricultural sector and global food security. However, challenges such as soil degradation, dependence on chemical fertilizers, and climate change necessitate more innovative and environmentally friendly approaches. Soil microorganisms play a significant role in improving crop productivity through biological mechanisms such as nitrogen fixation, organic matter decomposition, mycorrhizal symbiosis, and the production of bioactive compounds that protect plants from pathogens and abiotic stress. Microbiology-based biotechnology approaches, such as the use of biofertilizers and biopesticides, offer environmentally friendly solutions to address modern agricultural problems. This research aims to review the role of microorganisms in improving crop productivity, focusing on the application of microbiology-based biotechnology. The research method used is a literature study or meta-analysis of relevant literature and research in the last 10 years. The results of the discussion show that microorganisms such as Rhizobium, Azospirillum, Trichoderma, and mycorrhiza have a major contribution in improving soil fertility, crop yields, and plant resistance to environmental stress.